Urgensi Ilmu Nahwu dalam Memahami Nushus Syara'iyah - Suratno Suratno; Mustafa Muhammad; Dimas Muhammad Rizaldi; Samaa Abdul Aziz; Yoga Aji Ramadhan (Sanaamul Quran: Jurnal Wawasan Keislaman, 2022)
In the disruption era, it is very easy to convey ideas and information. Likewise, preaching and teaching religion, as well as consulting on religious law, is very easy to do. However, this is also accompanied by many people who are easy to fatwa, many people appear who talk about religious law without being accompanied by good religious knowledge. Whereas nushus syar'iyah speaks Arabic and can be understood with tools including the science of nahwu. The author researches with a literature review to determine the urgency of nahwu science in understanding nushus syar'iyah. This study proves that the science of nahwu has a very important role in the correct understanding of nushus syariyah. Reading nushus syariyah without this knowledge will be very dangerous because it can lead to wrong understanding. By mastering this knowledge, one will also be wiser towards differences of opinion among ulama, because one of the causes for the emergence of these differences of opinion is the difference in nahwu.